The social supply chain and the future high street. Issue 1 (11th January 2016) - Fletcher, Gordon; Greenhill, Anita; Griffiths, Marie; McLean, Rachel
Abstract : Purpose: – The purpose of this paper is to examine how independent social and commercial activities have developed in response to the perceived decline in the UK High Street and in response to the challenges of increasing digital retailing opportunities. This examination is undertaken through the lens of the social supply chain as a means to understanding, suggesting and expanding on current research regarding retailing and the UK High Street. The authors reveal some of the challenges being posed by the changing patterns of growth and consumption in cities and couple these with shifting supply chain trends. Design/methodology/approach: – A case study approach is used to explore the rapid advances and influence of digital technologies on businesses operating on the primary business street of suburban centre, towns or cities (described in the UK collectively as the "high street"). The research is conducted through the analytical lens of the social supply chain. Findings: – Theoretically extending the "social" in the social supply chain, the authors illustrate the usefulness of the nuanced concept of the "social supply chain" with two related strategies concerning delivery and balance. These strategies are themselves interlinked with the actions of co-creation, co-production and co-consumption. Examples of social supply chain strategies presented include retail businesses giving away something as an incentive, where the underlying requirement from the customer is that they will bring their own specialist product, skill or social network to a specified location (real or virtual). Originality/value: – For the purpose of this paper, the authors use two distinct strategies relating to delivery and balancing and in relation to the actions of co-creation, co-production and co-consumption to emphasise and analyse changes currently occurring in the UK High Street. The authors take a social supply chain management (SCM) perspective to undertake a systematic critical review of the various recent efforts undertaken by local governments, communities and trader groups to revitalise the High Street.